Answer:
[tex](x^{3} + 9\, x^{2} + 14\, x - 12)[/tex].
Step-by-step explanation:
Let [tex]p(x)[/tex] denote the polynomial in question.
The question states that dividing [tex]p(x)[/tex] by [tex](x + 3)[/tex] gives the quotient [tex](x^{2} + 6\, x - 4)[/tex] (with no remainder.) In other words:
[tex]\displaystyle \frac{p(x)}{x + 3} = x^{2} + 6\, x - 4[/tex].
Multiply both sides by [tex](x + 3)[/tex] to find an expression for the polynomial in question, [tex]p(x)[/tex]:
[tex]p(x) = (x^{2} + 6\, x - 4)\, (x + 3)[/tex].
Expand this expression to obtain:
[tex]\begin{aligned}p(x) &= (x^{2} + 6\, x - 4) \, (x + 3) \\ &= x\, (x^{2} + 6\, x - 4) \\ & \quad + 3\, (x^{2} + 6\, x - 4) \\ &= x^{3} + 6\, x^{2} - 4\, x \\ &\quad + 3\, x^{2} + 18\, x - 12 \\ &= x^{3} + 9\, x^{2} + 14\, x - 12\end{aligned}[/tex].